IMPLEMENTASI PLTMH UNTUK MENDUKUNG GREEN TECHNOLOGY DI DUSUN PETAPAN KLUNGKUNG - I Made Anom Adiaksa; I Ketut Suherman; Achmad Wibolo (Dharma: Jurnal Pengabdian Masyarakat, 2020)
The area of Petapan Hamlet is an upstream area where there are still many water sources as the main flow for downstream irrigation. There is one secondary stream with a fairly large channel size (2 m wide and 1 m deep). The flow velocity of this channel averages 1.6 m / sec with an average water depth in the dry season of 40 cm. The relatively large size of the channel results in a water flow of 1.26 liters / second. There is one place where the dimension of the channel shrinks for the distribution of irrigation to a width of 1 meter so that the correlation with a steady flow rate will increase. The people of Petapan Hamlet have built a tourism area based on green tourism with educational tourism as the main point. This tourism area is traversed by the subak water channel which will later be used as a place to play and educational tours about the subak irrigation system for tourists visiting this place. There is no supporting infrastructure in developing this tourism, both facilities and supporting facilities for the convenience of tourists in carrying out their activities The energy source that will be used to support the development of educational tourism is obtained from PLN sources. Lack of knowledge of the tourism community based on green tourism green technology (environment-based energy) which can be used as educational tourism              In 2019, a micro hydro generator in the form of a waterwheel has been built with an output power of 7000 kg / cm2. This power is obtained from the encouragement of water flow when it touches the blade of the wheel. This power is relatively large if it can be transmitted to generators. Problems that arise related to large power are small rotations. From the mill, the maximum rotation produced is 15 rpm. Making the rotation conversion by means of pulley reduction and gearbox resulting in a rotation of 1500 rpm. This obstacle is overcome by utilizing a DC type generator to lighten rotation and losses due to friction with 500 watts of power.